Efektivitas Model Pembelajaran Kooperatif dan Motivasi Terhadap Pemahaman Konsep Matematika - Virgana Virgana; Samin Samin; Rita Ningsih (JKPM (Jurnal Kajian Pendidikan Matematika), 2019)
This experiment is to know the understanding of the mathematical concept students are reviewed from a model of cooperative learning and motivational learning. The research Model uses a 2 x 2 factorial design. The research sample is 60 Grade 9 students from first junior high school, South Jakarta academic year 2018--2019. The two-way Analysis of variance (ANOVA) is used in this study. The effectiveness of the learning management is determined by the calculation of effect size, while the results of the study are as follows: There is a influence of cooperative learning model interaction and motivation to learn to understand mathematical concepts, Influence of cooperative learning model to understand the concept of mathematics, the influence of motivation to learn to understand the concept of mathematics, and learning model of cooperative learning the type of Student Teams Achievement Devision (STAD) has High effectiveness towards understanding students ' mathematical concepts. With the conclusion that understanding the concept of mathematics in junior high school is influenced by the use of cooperative variation and learning motivation of students. This research is expected to be beneficial for further research to improve the mastery of students ' mathematical concepts.